Food Fights : How History Matters to Contemporary Food Debates - Booker, Matthew Morse, 1968-; Ludington, Charles (Book collections on Project MUSE., 2019)
"What we eat, where it is from, and how it is produced are vital questions in today's America. We think seriously about food because it is freighted with the hopes, fears, and anxieties of modern life. Yet critiques of food and food systems all too often sprawl into jeremiads against modernity itself, while supporters of the status quo refuse to acknowledge the problems with today's methods of food production and distribution. Food Fights sheds new light on these crucial debates, using a historical lens. Its essays take strong positions, even arguing with one another, as they explore the many themes and tensions that define how we understand our food--from the promises and failures of agricultural technology to the politics of taste"--